Statistical quality control to emission uniformity in micro sprinkler with autonomous photovoltaic pumping (Research, Society and Development, 2021)
This work aimed to evaluate a microsprinkler irrigation system using photovoltaic energy without energy storage. The influence of photovoltaic pumping on irrigation was evaluated from the Emission Uniformity, Shewhart control charts and Process Capacity. The experiment consisted of two amorphous photovoltaic panels connected in parallel, directly connected to a water pump, where the flow of the pumping system was carried out through a ½” tube (main line), to the irrigation system composed of four microsprinklers. The voltage and current parameters were collected, and the power of the photovoltaic system was calculated, while for the irrigation system the pressures of the four microsprinklers were measured to later calculate the flow rate of the irrigation system. The experiment was conducted at the State University of Western Paraná, UNIOESTE, where 25 days of collection were carried out, in the open, at four different times, from 10:00 am to 11:00 am, from 11:05 am to 12:05 pm, from 2:00 pm to 3:00 pm and from 3:05 pm to 4:05 pm . Power generation presented a low coefficient of variation throughout the day, which resulted in flow and pressure stability, culminating in an Emission Uniformity (UE) value qualified as excellent (93.66%) according to the ASAE. The values of energy generation, flow, pressure, and emission uniformity presented a Process Capacity (CP) value above 1.33, defining the process as capable and adequate throughout the analyzed period.